New Trends in Sport and Exercise Medicine - Galli, Daniela (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The practice of regular physical activity has been proposed as a determinant in many disciplines, from wellness to physiotherapy; in fact, it reduces the risks of cardiovascular diseases and diabetes. Moreover, physical exercise decreases the incidence of some types of cancer, such as breast and colon cancer. Finally, rehabilitation protocols need correct exercise training to reach the complete "return to play" of patients. Unfortunately, the mechanisms associated with the beneficial effects of physical activity are still under study. Therefore, advances in all aspects of sport and exercise medicine will be relevant for physicians, recreational sport practitioners and elite athletes. This was the aim of this Special Issue, "New trends in sport and exercise medicine", which achieved great success. Sixteen papers have been published, which are briefly described below. They range from mobile applications in physiotherapy to changes in bioactive lipids in half-marathoners. However, sport and exercise medicine are broad subjects and require more papers to clarify their different aspects. Therefore, we proposed a new Special Issue to continue on this path and gain new insights into sport and exercise medicine.